EFEKTIVITAS PELATIHAN INTENSIF MAKHARIJUL HURUF DAN HUKUM TAJWID DALAM MENINGKATKAN KETEPATAN PELAFALAN AYAT AL-QUR'AN PADA PESERTA DIDIK KELAS III SD PLUS MARHAMAH - Rina Windari; Martin Kustati; Nana Sepriyanti (STKIP Subang, 2026)
The ability to read the Qur'an correctly in accordance with makharijul huruf (articulation points of Arabic letters) and the rules of tajwid is a fundamental competency that students must possess. However, errors in pronouncing hijaiyah letters and applying tajwid rules are still prevalent among third-grade students of SD Plus Marhamah, resulting in suboptimal accuracy of Qur'anic recitation. This study aims to determine the effectiveness of intensive training in makharijul huruf and tajwid rules in improving the accuracy of Qur'anic verse pronunciation. A quantitative approach with a quasi-experimental one-group pretest-posttest design was employed. Thirty third-grade students were selected through total sampling as research subjects. Data were collected through practical Qur'an reading tests, assessed using a validated rubric instrument covering makharijul huruf accuracy, tajwid application, reading fluency, and overall pronunciation. Data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, the Paired Sample t-Test, and N-Gain Score analysis. Results revealed a significant improvement in students' Qur'an reading accuracy, with the mean score rising from 66.20 (pretest) to 87.53 (posttest). The Paired Sample t-Test yielded a significance value of 0.000 (p < 0.05), indicating a statistically significant difference before and after training. The N-Gain Score of 0.63 placed the intervention in the moderately effective category. These findings demonstrate that intensive training in makharijul huruf and tajwid rules is an effective instructional strategy for improving Qur'anic pronunciation accuracy among elementary school students.